MunasÄbat Al-ÄyÄt Wa Al-Suwar - Rahmawati, Rahmawati (Jurnal Adabiyah, 2013)
Understanding quranic munasabah (co-relation) is very urgent in interpreting the verse of al-Qurâan. Itâs because al-Qurâan has integrated meaning and text that have to be analyzed based on asbab al-nuzul, interrelation between ayat and surah. Munasabah al-Qurâan as study was firstly introduced by Imam Abu Bakar al-Naisabury but his effort was not seriously paid attention by the experts. But in next era there were ulamas who wrote munÄsabah. The kinds of munÄsabah are as follow: munÄsabah between surah and previous surah, surah and its goal, relation between verse and previous verse, relation between sentence and centence in one verse, and relation between the closer of verse and its contents.